2016
DOI: 10.1099/jgv.0.000311
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-33a disturbs influenza A virus replication by targeting ARCN1 and inhibiting viral ribonucleoprotein activity

Abstract: In order to explore the roles of microRNA(s) [miRNA(s)] in the influenza A virus life cycle, we compared the miRNA profiles of 293T and HeLa cell lines, as influenza A virus can replicate efficiently in 293T cells but only poorly in HeLa cells. We analysed differentially expressed miRNAs and identified five, including miR-33a, that could disturb influenza A virus replication significantly. Using TargetScan analysis, we found that ARCN1 could be a potential target of miR-33a. To confirm whether miR-33a could tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 36 publications
0
21
0
1
Order By: Relevance
“…Previous evidence has demonstrated that several miRNAs, including miR‐33a, miR‐302c, and miR‐let‐7c, are involved in the replication of IAV . It has also been shown that miR‐146a is induced via a wide range of viral infections, and probably miR‐146a contributes to virus replication.…”
Section: Mir‐146a In Influenzamentioning
confidence: 99%
See 1 more Smart Citation
“…Previous evidence has demonstrated that several miRNAs, including miR‐33a, miR‐302c, and miR‐let‐7c, are involved in the replication of IAV . It has also been shown that miR‐146a is induced via a wide range of viral infections, and probably miR‐146a contributes to virus replication.…”
Section: Mir‐146a In Influenzamentioning
confidence: 99%
“…50 Previous evidence has demonstrated that several miRNAs, including miR-33a, miR-302c, and miR-let-7c, are involved in the replication of IAV. [99][100][101] It has also been shown that miR-146a is induced via a wide range of viral infections, and probably miR-146a contributes to virus replication. However, studies on the involvement of miR-146a in IAV infection are insufficient, and the related underlying molecular mechanisms of influenza infectious cycle remain unknown.…”
Section: Mir-146a In Influenzamentioning
confidence: 99%
“…Many studies have demonstrated the significant effect of miRNAs on modulating influenza virus infection. For examples, miR‐33a was suggest to disrupt influenza A virus (IAV) replication by targeting APCN1 (Hu et al, ); miR‐34a contributed to influenza virus‐mediated apoptosis by binding to BAX (Fan & Wang, ); and miR‐let‐7c targeted and inhibited M1 expression of the H1N1 influenza virus (Ma et al, ). Although several studies linked miRNAs to type I IFN production mediated by RIG‐I in influenza virus infection (miR‐144, miR‐485, and miR‐136) (Ingle et al, ; Rosenberger et al, ; Zhao et al, ), the underlying regulation of the type I IFN‐mediated antiviral response by miRNAs during influenza virus infection remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that a liver-specific microRNA, miR-122, can promote the replication of hepatitis C virus (HCV) [13,14], while miR-199a inhibits viral replication by binding to HCV genomic RNA [15]. Similarly, miR-33a can inhibit viral replication in influenza A by suppressing ARCN1 expression and weakening viral ribonucleoprotein activity [16], and miR-32 plays a crucial role in a the antiviral response to primate foamy virus type 1 (PFV-1) by targeting ORF2 of the viral genome [17]. Additionally, the EBNA1 protein of Epstein-Barr virus (EBV) promotes EBV latency by inducing the expression of let-7 miRNAs [18] and, of particular note, miR-181 inhibits PRRSV replication by targeting both viral genomic RNA and cellular receptor CD163 [19,20].…”
Section: Introductionmentioning
confidence: 99%